2017
DOI: 10.1080/08923973.2017.1285919
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivoall-transretinoic acid modulates NO production and regulates IL-6 effect during rheumatoid arthritis: a study in Algerian patients

Abstract: Rheumatoid arthritis (RA) is a chronic autoimmune disease. The pathophysiology of RA implicates several mediators such as nitric oxide (NO) and cytokines such as interleukin-6 (IL-6), which is deeply involved in the main characteristics of RA. Furthermore, all-trans retinoic acid (ATRA) is an active vitamin A derivative well-known to have diverse immunomodulatory actions. In our study, we investigated first, the ex vivo immunomodulatory potential of ATRA on NO pathway by peripheral blood mononuclear cells (PBM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
2
3
0
Order By: Relevance
“…We first found positive correlations between levels of IL-6 and that of CRP or NO in agreement with previous studies linking IL-6 to other inflammatory mediators in COPD including CRP (Garcia-Rio, et al, 2010;Heinrich, et al, 1990;Kolsum, et al, 2009). The ability of IL-6 to induce NO production and iNOS expression has been recently demonstrated in PBMCs of patients with rheumatoid arthritis (Arroul-Lammali, et al, 2017) and in femoris muscles in COPD patients (Agusti, 2005). We also found negative correlations between FEV 1 (% predicted) values and plasmatic levels of NO and IL-6 (r=-0 =-0.55 and r=-0.427, respectively), reinforcing the concept that systemic inflammation drives airflow obstruction in COPD patients.…”
Section: Discussionsupporting
confidence: 91%
“…We first found positive correlations between levels of IL-6 and that of CRP or NO in agreement with previous studies linking IL-6 to other inflammatory mediators in COPD including CRP (Garcia-Rio, et al, 2010;Heinrich, et al, 1990;Kolsum, et al, 2009). The ability of IL-6 to induce NO production and iNOS expression has been recently demonstrated in PBMCs of patients with rheumatoid arthritis (Arroul-Lammali, et al, 2017) and in femoris muscles in COPD patients (Agusti, 2005). We also found negative correlations between FEV 1 (% predicted) values and plasmatic levels of NO and IL-6 (r=-0 =-0.55 and r=-0.427, respectively), reinforcing the concept that systemic inflammation drives airflow obstruction in COPD patients.…”
Section: Discussionsupporting
confidence: 91%
“…In the TNF-a experiment, we observed that TNF-a stimulation could induce the expression of NO. But after adding ATRA, the production of NO was inhibited without dose dependence, similar to the study conducted by Algerian (16).…”
Section: Discussionsupporting
confidence: 83%
“…Researches showed that ATRA intervention can reduce inflammation in rheumatoid arthritis (13,14), promoting the expression of anti-inflammatory Foxp3 of regulatory T cells and inhibit pro-inflammatory Th17 cells (15). ATRA can also down-regulate the production of NO and the expression of iNOS in peripheral blood mononuclear cells of patients with RA mediated by IL-6 (16), reducing proliferation, migration and invasion of FLS in rheumatoid arthritis. Our preliminary animal experiments have also demonstrated that ATRA can alleviate joint inflammation in CIA rats, inhibiting the expression of inflammatory cytokines and proteins associated with cartilage damage, and have a potentially beneficial effect on RA (17).…”
mentioning
confidence: 99%
“…Furthermore, ATRA inhibited nitric oxide (NO), a radical gas produced during several autoimmune diseases, which is induced by action of IL-6 on peripheral blood mononuclear cells (PBMCs) from Algerian patients with RA (20). In addition, a recent study also showed that ATRA ameliorated joint damage and loss of function in patients with RA by reducing the proliferative, migratory and invasive capacity of RA FLS (21).…”
mentioning
confidence: 99%